Economic crises and the breakdown of authoritarian regimes Indonesia and Malaysia in comparative perspective - Pepinsky, Thomas B. (Cambridge University Press, 2009)
Why do some authoritarian regimes topple during financial crises, while others steer through financial crises relatively unscathed? Thomas B. Pepinsky uses the experiences of Indonesia and Malaysia and the analytical tools of open economy macroeconomics to answer this question.